Land and life in Timor-Leste : ethnographic essays - McWilliam, Andrew; Traube, Elizabeth G. (Monographs in anthropology., 2011)
"This volume brings together a collection of papers from a diverse field of international scholars exploring the multiple ways that East Timorese communities are making and remaking their connections to land and places of ancestral significance. The work is explicitly comparative and highlights the different ways Timorese language communities negotiate access and transactions in land, disputes and inheritance especially in areas subject to historical displacement and resettlement. Consideration is extended to the role of ritual performance and social alliance for inscribing connection and entitlement. Emerging through analysis is an appreciation of how relations to land, articulated in origin discourses, are implicated in the construction of national culture and differential contributions to the struggle for independence."--Publisher's description